Why mosquitoes buzz in people's ears : a West African tale - Aardema, Verna; Dillon, Leo; Dillon, Diane (New York : Dial Press, 1975)
A retelling of a traditional West African tale that reveals how the mosquito developed its annoying habit.
Keywords: Folklore -- Africa, West; Animals -- Folklore